Keterampilan Berbicara Bahasa Jerman Secara Mandiri Melalui Aplikasi Mobile Learning Fun Easy Learn - Syifa Azzahrah; Muh Anwar; Mantasiah R (Universitas Negeri Makassar, 2023)
Abstract. This study aims to determine the planning, implementation and results of improving the German speaking ability of class XI IBB students of SMAN 8 Bulukumba through the Mobile Learning Fun Easy Learn application. This research is a classroom action research which consists of two cycles, each cycle consisting of the stages of planning, implementing, observing and reflecting. The research data consisted of two types of data, namely qualitative data which was a description of the results of the implementation and observations during the learning process and quantitative data in the form of students' speaking ability test results presented in the form of percentages. The average score of the speaking ability of class IX IBB students in cycle I was 50 and in cycle II it increased to 75.78. The results of this study indicate that the Mobile Learning Fun Easy Learn application can improve the ability to speak German in class XI IBB students of SMA Negeri 8 Bulukumba.Keywords: Class Action Research, Speaking Skills, Fun Easy Learn.